Rodent Assemblage Composition as Indicator of Fire Severity in a Protected Area of South-Central Chile - Vergara-Egert, P (Blackwell Publishing, 2021)
Fires have a considerable impact on biological communities and ecosystems, within which the assessment of burned habitats requires consideration of indicator species or assemblages useful for monitoring. The short-term effects of fires can be easily deduced from analysing assemblages of animals with short generation times and high fertility rates, such as rodents. Here, we evaluated the effect of fire severity in a protected area of southern Chile on abundance, composition and diversity of rodent assemblages. We sampled rodents and vegetation variables during summer and fall over two years (2017 and 2018) in forest stands with different levels of fire severity (high, low and unburned stands). Changes in diversity and abundance were found between unburned and burned stands, with these differences being more noticeable during the fall of the first year. Abundances of rodent species exhibited marked fluctuations over the study period, but two species consistently decreased their abundances as fire severity increased, and with the absence of one species in burned stands. The adverse fire effects were less evident during the second year due to the overall low capture rates (1.3–1.9%). Rodent species were differently affected by fire, with Irenomys tarsalis (arboreal rat) being the species most sensitive to fires. The effect of fire severity on abundance of rodent species was associated with changes in the vegetation variables, where dead wood, canopy and herb cover showed a low correlation (R = 0.147). Our results suggest that fires of high severity cause important disturbances on habitat and food resources that result in short-term effects on the rodent assemblage. Fires apparently act as an ecological filter for the more specialised species while offering an opportunity for the settlement of generalist species. Hence, the monitoring of rodent species differing in their ecological traits, such as food habits and space use, offers an opportunity for assessing the short-term recovery patterns of wildlife after fire disturbances. © 2020 Ecological Society of Australia